2017
DOI: 10.1002/elps.201700188
|View full text |Cite
|
Sign up to set email alerts
|

Production of β‐Lactoglobulin hydrolysates by monolith based immobilized trypsin reactors

Abstract: Tryptic hydrolysis of β-Lactoglobulin (β-Lg) is attracting more and more attention due to the reduced allergenicity and the functionality of resulting hydrolysates. To produce hydrolysates in an economically viable way, immobilized trypsin reactors (IMTRs), based on polymethacrylate monolith with pore size 2.1 μm (N1) and 6 μm (N2), were developed and used in a flow-through system. IMTRs were characterized in terms of permeability and enzymatic activity during extensive usage. N1 showed twice the activity comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…We were not able to find a study directly comparing axial flow and radial flow guided monolithic catalysts. In a study of Naldi et al [41], 4.5 mg trypsin was reported to be immobilized on per milliliters CIM ® ‐ALD monolith disk (axial flow), and around 5.0 mg trypsin was immobilized on per milliliters CIM ® ‐ALD tubular monolith column (radial flow) in our previous work [44]. This slight difference in the amount of immobilized trypsin is more attributed to the varied immobilization protocols or calculation methods, rather than the choice between disk and tubular columns.…”
Section: Characteristics Of Polymer Monoliths Affecting the Immobilization Of Enzymesmentioning
confidence: 99%
See 3 more Smart Citations
“…We were not able to find a study directly comparing axial flow and radial flow guided monolithic catalysts. In a study of Naldi et al [41], 4.5 mg trypsin was reported to be immobilized on per milliliters CIM ® ‐ALD monolith disk (axial flow), and around 5.0 mg trypsin was immobilized on per milliliters CIM ® ‐ALD tubular monolith column (radial flow) in our previous work [44]. This slight difference in the amount of immobilized trypsin is more attributed to the varied immobilization protocols or calculation methods, rather than the choice between disk and tubular columns.…”
Section: Characteristics Of Polymer Monoliths Affecting the Immobilization Of Enzymesmentioning
confidence: 99%
“…In addition, another study [40] directly correlated the sequence recovery rate to the enzymatic activity of trypsin‐IMER, and indicated that improving digestion flow rates up to 0.4 mL/min increased the reaction rate, which is quite disputable. Here, we try to sort out these references and give a critical discussion including our previous works [42,44].…”
Section: Parameters Affecting the Performances Of Polymer Monoliths‐based Immobilized Enzyme Reactorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, the peptide analysis differed between the immobilized trypsin and the free trypsin, demonstrating the impact of immobilization methods on enzyme selectivity. 111 Trypsin has also been immobilized on renewable supports for whey protein hydrolysis, including spent grain and lignocellulose. 112,113 Multipoint covalent attachment was used to tether trypsin (from porcine pancreas) to spent grain, and retained greater than 90% activity after 5 cycles of reuse, as measured by the synthetic substrate, N -α-benzoyl- dl -arginine- p -nitroanilide.…”
Section: Applications Of Immobilized Enzymes In Food Waste Stream Valmentioning
confidence: 99%